Wildfire - Clark, Mavis Thorpe (Hornsby, N.S.W. : Hodder & Stoughton (Australia) in association with Brockhampton Press, 1973)
Chronicles the terrifying events of the day that an uncontrolled wildfire sweeps across the countryside and records the reactions of five youngsters caught in it.
For adolescents.
Keywords: Children's stories in English. Australian writers, 1945-. Texts; Forest fires -- Australia -- Juvenile fiction; Friendship -- Juvenile fiction; Interpersonal relations in adolescence -- Juvenile fiction; Young adult fiction, Australian; Adventure stories